2007
DOI: 10.1111/j.1440-1681.2007.04608.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT7, NEUROGENESIS AND ANTIDEPRESSANTS: A PROMISING THERAPEUTIC AXIS FOR TREATING DEPRESSION

Abstract: SUMMARY1. There is mounting evidence that a wide range of antidepressants share the common feature of increasing hippocampal neurogenesis. The specificity of this association has suggested that an ability to increase neurogenesis might be a useful paradigm to screen for compounds with antidepressant activity.2. The hope of developing better antidepressants has stimulated research into the molecular control of neurogenesis and here we summarize some of the recent findings. We also review recent work that highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…Furthermore, 5-HT 7 −/− mice spend less time in REM sleep (Hedlund et al 2005). Finally, there is some evidence that 5-HT 7 receptor antagonism may affect neuronal morphology (Kvachnina et al 2005) and stimulate hippocampal neurogenesis alone (Nandam et al 2007), (Kodama et al 2004) or synergistically with another antidepressant (Xu et al 2006). This is consist with antidepressant activity, since antidepressant efficacy has been correlated with hippocampal neurogenesis in some (Santarelli et al 2003), (Malberg et al 2000), but not all (Holick et al 2008), studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-HT 7 −/− mice spend less time in REM sleep (Hedlund et al 2005). Finally, there is some evidence that 5-HT 7 receptor antagonism may affect neuronal morphology (Kvachnina et al 2005) and stimulate hippocampal neurogenesis alone (Nandam et al 2007), (Kodama et al 2004) or synergistically with another antidepressant (Xu et al 2006). This is consist with antidepressant activity, since antidepressant efficacy has been correlated with hippocampal neurogenesis in some (Santarelli et al 2003), (Malberg et al 2000), but not all (Holick et al 2008), studies.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies with 5-HT 7 receptor antagonists, such as SB 269970, have revealed a potential role for 5-HT 7 receptor activation in novel object recognition (Ballaz et al, 2007), stereotypic behavior (Hedlund and Sutcliffe, 2007), as well as anxiogenic and depressive-like behavior (Wesolowska et al, 2006, Nandam et al, 2007). Moreover, 5-HT 7 knockout mice exhibit impaired contextual fear conditioning (Roberts et al, 2004), and decreased immobility in the Porsolt swim test (Guscott et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lurasidone's high affinity and antagonistic activity at 5-HT 7 receptors may support its utility in the treatment of major depressive disorders (MDD) or in the treatment of bipolar depression since these receptors have increasingly attracted attention as novel pharmacotherapy targets for depression [79,80]. The ability of lurasidone to reduce immobility in animals model of depression add further support for its antidepressant actions.…”
Section: Expert Opinionmentioning
confidence: 98%